Tingkat Kesuburan Muara Tukad Aya, Jembrana Bali Berdasarkan Kelimpahan Plankton dan Ketersediaan Nutrien - Siagian, Josua; Arthana, I Wayan; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science, 2019)
River estuaries have characteristics that were directly related to the sea, resulting of mixing wate r which result ing in a unique in terms of complex and dynamic environmen t and community structure of biota that was different from other waters . The purpose of this study was to determine the fertility level of Muara Tukad Aya base on the abundance of plankton . This research was conducted in February-March 2019 using descriptive quantitative methods. The average value of water quality in the three stations, namely turbidity ranges from 11.5 to 12.48 NTU, temperature 27.61-31.20C, current speed 0-0.2 m / s, brightness 72.32-86.8 cm, salinity 16.0-17.94 ppt, pH 8.02-8.14, Nitrate 0.5-1.05 mg / L, Phosphate 0.08-0.2 mg / L, DO 7.7- 8.8 (mg / L). The abundance of phytoplankton was found in 37 genera, the total abundance at station I (upstream of the estuary) was 1501 cells / l, at station II (open area of estuary) was 1322 cells / l and station III (close area of the estuary) with an abundance of 833 cells / l. Zooplankton abundance was 6 genera, where total abundance at station I was 9 ind / L, station II was 11 ind / l while station III was 10 ind / l . Water quality parameter values at estuary Tukad are still good and optimum except phosphate levels , The abundance of phytoplankton with nitrite and nitrate has a close relationship with the correlation coefficient -0.9014 and 0.8994.